DETECTION OF ANTIBIOTIC RESIDUES IN THE LIVER AND KIDNEY OF INTENSIVE BROILERS AND KUB CHICKENS REARED ACCORDING TO ANIMAL WELFARE STANDARDS - Cathy Beatrice Evelyn Purba; Kadek Karang Agustina; Tjok Gde Oka Pemayun (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
The increasing public demand for chicken meat has driven the intensification of broiler poultry farming, which risks increasing the use of antibiotics and the presence of residues in animal-derived food products. Uncontrolled antibiotic use can trigger the presence of residues that endanger consumer health. This study aimed to detect and compare the prevalence of antibiotic residues in the liver and kidney organs of intensively reared broiler chickens and Kampung Unggul Balitbangtan (KUB) chickens raised according to animal welfare standards. This research was an analytical observational study with a comparative cross-sectional design. A total of 20 liver and kidney samples were collected using purposive sampling and tested using the bioassay method at the Balai Besar Veteriner (BBVet) Denpasar to detect residues of penicillin, tetracycline, macrolide, and aminoglycoside. The results showed that the prevalence of antibiotic residues in intensive broiler chickens was 10% with findings of penicillin group residues, while all KUB chicken samples showed negative results. Statistical analysis using the Chi-Square test indicated that there was no significant difference between the two groups (p-value=0.305). The animal welfare-based rearing system in KUB chickens demonstrates better food safety potential compared to the intensive system due to the absence of antibiotic residues. The implementation of animal welfare standards plays an important role in maintaining livestock health and the quality of animal products naturally. It is recommended for farmers to begin implementing animal welfare standards to reduce dependence on antibiotic use and ensure food safety.